1991
DOI: 10.1002/bin.2360060204
|View full text |Cite
|
Sign up to set email alerts
|

Conversational skills training with a chronically hospitalized psychiatric inpatient

Abstract: While conversational skills training has been conducted with select psychiatric populations, it has rarely been used with severely debilitated inpatients. The purpose of this study was to use a multiple baseline design across conversational components to evaluate the effectiveness of a conversational skills training package to enhance the conversational repertoire of a severely impaired inpatient. Audiotaped conversations with a standard confederate were evaluated for the frequency of questions, self-disclosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The results of this study support the findings of the original Paul and Lentz report (Paul & Lentz, 1977), single-subject designs (Curran et al, 1991;Himadi & Kaiser, 1992;Osborne & Himadi, 1990), and more-recent effectiveness studies (Baldwin et al, 1992;Beck et al, 1991;Menditto et al, 1991;Menditto et al, 1996;Silverstein et al, 2006;Silverstein et al, 2009). Furthermore, findings in this study are in keeping with the American Psychological Association's Task Force on Serious Mental Illness and Emotional Disturbance's (2007) designation of the SLP as a best practice for inpatient treatment of psychosis as well as with the inclusion of SLPs in the latest Patient Outcomes Research Team recommendations (Dixon et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study support the findings of the original Paul and Lentz report (Paul & Lentz, 1977), single-subject designs (Curran et al, 1991;Himadi & Kaiser, 1992;Osborne & Himadi, 1990), and more-recent effectiveness studies (Baldwin et al, 1992;Beck et al, 1991;Menditto et al, 1991;Menditto et al, 1996;Silverstein et al, 2006;Silverstein et al, 2009). Furthermore, findings in this study are in keeping with the American Psychological Association's Task Force on Serious Mental Illness and Emotional Disturbance's (2007) designation of the SLP as a best practice for inpatient treatment of psychosis as well as with the inclusion of SLPs in the latest Patient Outcomes Research Team recommendations (Dixon et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Several reports in the last few decades have documented positive responses to SLPs for a variety of recovery outcome domains, including reduction of aggressive behavior (Beck, Menditto, Baldwin, Angelone, & Maddox, ; Silverstein et al, ) and polydipsia (Baldwin, Beck, Menditto, Arms, & Cormier, ) as well as improvement in attentional capacity (Menditto, Baldwin, Oneal, & Beck, ; Silverstein et al, ) and small sample demonstrations of increases in overall adaptive behavior (Menditto et al, ). Single‐case studies have demonstrated decreased belief in delusional material (Himadi & Kaiser, ) and improved adaptive behaviors such as care of one's living environment (Osborne & Himadi, ) and conversational skills (Curran, Himadi, & Donahue‐Bennett, ) in response to intervention on SLP units.…”
mentioning
confidence: 99%